ANALISIS PENGENDALIAN PERSEDIAAN PAKAN TERNAK SAPI PADA PT INDO PRIMA BEEF DI KABUPATEN LAMPUNG TENGAH - Yustika Yustika; Adia Nugraha; Rabiatul Adawiyah (Lampung University, 2021)
The purposes of this study are to analyze cost-efficient control of feed raw material inventory, anticipate shortages of supply, determine the correct time frame for reordering raw materials at the feedlot company PT Indo Prima Beef using the Economic Order Quantity (EOQ) mathematical model and determine the inventory value of raw materials with the First In First Out (FIFO) assessment model. Data collection was carried out in March-May 2020 using a case study method. The data used were primary data collected using questionnaires and secondary data from literature studies. The results showed that the inventory cost applied by PT Indo Prima Beef was different from the calculation of the EOQ model. According to EOQ analysis, the largest amount of safety stock is corn sugarcane as much as 139,725.95 kg, and the lowest amount is salt around 870.63 kg. The reorder point for PT Indo Prima Beef with the largest amount was dry onggok as much as 139,926 kg, while the lowest amount was 724.87 kg of salt. PT Indo Prima Beef uses a perpetual recording system with the First In First Out (FIFO) inventory valuation method with a total raw material inventory value of IDR2,129,685,820 in one year.Key words: EOQ,FIFO, inventory, supplies